Self-Reported Quality of Life and Depressive Symptoms in Children, Adolescents, and Adults with Duchenne Muscular Dystrophy: A Cross-Sectional Survey Study - Elsenbruch, Sigrid; Schmid, Julia; Lutz, Soeren; Geers, Brigitte; Schara, Ulrike (Neuropediatrics, 2013)
Aim We aimed to address the impact of Duchenne muscular dystrophy (DMD) on self-reported health-related quality of life (HRQOL) and depressive symptoms in different age groups of patients to discern a possible need for improved psychosocial support or counseling.Methods In a German clinic for pediatric neurology, we performed a cross-sectional questionnaire survey in a total of 50 patients with DMD (i.e., n = 15 children aged 8 to 12 years; n = 11 adolescents aged 13 to 16 years; n = 24 young adults aged 17 to 23 years). We assessed self-reported HRQOL and symptoms of depression using validated, age-appropriate instruments.Results In children with DMD, virtually all aspects of HRQOL were significantly impaired when compared with published normative data for boys with other chronic illnesses. On the contrary, adolescents and adults with DMD did not differ from published normative data in psychosocial areas of HRQOL, despite significant reductions in physical aspects of HRQOL. Clinically relevant depressive symptoms were not observed in either age group.Interpretation DMD may not always be associated with impaired psychosocial HRQOL and clinical depression, although progressive physical impairment leads to reduced physical aspects of HRQOL. Only children with DMD demonstrated marked impairments in psychosocial aspects of HRQOL calling for psychosocial interventions tailored to this age group.
Keywords: Duchenne muscular dystrophy; quality of life; depression